Teachers’ AI literacy: Perspectives from the technical, pedagogical, ethical, and critical dimensions - Ratih Laily Nurjanah; Sri Waluyo (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2026)
This study investigates the AI literacy of lecturers of English as a Foreign Language (EFL) at Indonesian higher education institutions across four analytically distinct dimensions: technical, pedagogical, ethical, and critical. Employing a descriptive-exploratory qualitative design, data were collected through semi-structured Zoom interviews with 20 EFL lecturers aged 25–35 who had at least 2 years of teaching experience. Interviews were audio-recorded, transcribed, and analyzed through reflexive thematic analysis. The findings reveal a recurring pattern of uneven AI literacy development across all four dimensions. Technically, participants demonstrated functional familiarity with AI tools without a foundational understanding of the generative mechanisms underlying these systems. Pedagogically, AI use was largely confined to lesson preparation and task automation rather than the intentional redesign of instructional strategies. Ethically, participants’ awareness was concentrated on academic integrity, while data privacy and algorithmic bias remained substantially underexplored. Critically, evaluation practices for AI-generated content varied considerably, with only a minority of participants applying systematic screening protocols. These findings collectively indicate that the EFL lecturers in this study possessed AI literacy at a formative stage—adequate for surface-level tool engagement but insufficient to support reflective, ethical, and pedagogically transformative AI integration. The study calls for professional development programs that address all four dimensions of AI literacy, with particular attention to conceptual understanding, critical evaluation, and ethical awareness in the Indonesian EFL higher education context.